2014
DOI: 10.1021/nn405923b
|View full text |Cite
|
Sign up to set email alerts
|

Photomodulated Fluorescence of Supramolecular Assemblies of Sulfonatocalixarenes and Tetraphenylethene

Abstract: Self-assembled fluorescent nanoparticles responding to specific stimuli are highly appealing for applications such as labels, probes, memory devices, and logic gates. However, organic analogues are challenging to prepare, due to unfavorable aggregation-caused quenching. We herein report the preparation of self-assembled fluorescent organic nanoparticles in water by means of calixarene-induced aggregation of a tetraphenylethene derivative (QA-TPE) mediated by p-sulfonatocalix[4]arenes. The self-assembled nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
111
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 89 publications
1
111
0
1
Order By: Relevance
“…[8][9][10] For example, they induced the aggregation of tetraphenylethene derivatives to strongly fluorescent nanoassemblies 11 and their emission properties could be tuned by irradiation with UV light. 12 The binding to SCXn facilitates the aggregation of aromatic or amphiphilic molecules. [13][14][15][16][17] The interaction of the macrocycle homologue comprised of four sulfonatophenol units (SCX4) with a natural cationic protein, protamine resulted in supramolecular vesicle which disintegrated in a controlled manner upon addition of trypsine.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] For example, they induced the aggregation of tetraphenylethene derivatives to strongly fluorescent nanoassemblies 11 and their emission properties could be tuned by irradiation with UV light. 12 The binding to SCXn facilitates the aggregation of aromatic or amphiphilic molecules. [13][14][15][16][17] The interaction of the macrocycle homologue comprised of four sulfonatophenol units (SCX4) with a natural cationic protein, protamine resulted in supramolecular vesicle which disintegrated in a controlled manner upon addition of trypsine.…”
Section: Introductionmentioning
confidence: 99%
“…SC4A not only induced compact packing between anthracenes but also inhibited the fluorescence quenching of AnPy, which is favorable for photosensitization. Interestingly, the photodecomposition of aggregated AnPy was significantly promoted, while it was reported that the fluorescence of photosensitizers could be generally self-quenched after aggregation, 16 resulting in greatly reduced ability for singlet oxygen generation and lower photoreactivity. 17 The supramolecular assembly exhibited efficient photolysis with visible light in the presence of exogenous photosensitizers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[5][6][7] Calixarenes form metal nanoparticles, [8][9][10] e.g. AuNPs 8,9 and AgNPs, 10 as well as organic NPs, 11 and serve for construction of sensors; [12][13][14] they also may be used as extractants of f-elements. 15,16 The present paper is a continuation of our previous reviews concerning covalently and noncovalently bound calixarene assemblies, 17 calixarenes functionalized at wide and narrow rims, 18 calixarenes substituted at meso positions, 19 calixarene complexes with metal ions, 20 as well as calixarenes and resorcinarenes.…”
Section: Introductionmentioning
confidence: 99%